A new species of the ant spider genus Suffasia (Araneae: Zodariidae) from the Western Ghats, India with a key to the species of the genus - Sudhikumar, Ambalaparambil V.; Jocqué, Rudy; Sebastian, Pothalil A. (Zootaxa, 2009)
Suffasia keralaensis, a new species in the spider family Zodariidae from the Western Ghats in India is described. It can be diagnosed from other members of the genus by oval spermathecae in the female and by the presence of three cymbial pits and long curved embolus with pointed tip of the male palp. A diagnostic key to both male and female species so far reported of the genus Suffasia is provided.